Anisotropic Hybrid Hydrogels Constructed via the Noncovalent Assembly for Biomimetic Tissue Scaffold. (10th February 2022) - Lin, Xinghuan; Xing, Xin; Li, Shanshan; Wu, Xiaoyi; Jia, Qiaoqiao; Tu, Hu; Bian, Haolin; Lu, Ang; Zhang, Lina; Yang, Hongye; Duan, Bo
Abstract: Anisotropic structure is key for exploring the biomimetic functions of anisotropic hydrogels. However, the anisotropic hydrogel study should not be limited to its architecture design but must include the understanding and improvement of the internal interaction among their components. Herein, a noncovalent mediated assembly strategy is proposed to simultaneously improve the chitin chain mobility and enhance the interfacial interaction, for achieving anisotropic chitin/2D material (molybdenum disulfide and brushite as example) hydrogels via mechanical deformation. Tannic acid (TA) is used to i) introduce the dynamic noncovalent crosslinking structure among the chitin chains for affording considerable molecular mobility to allow chitin chains alignment under mechanical deformation; ii) enhance chitin–2D interfacial interaction for benefiting 2D materials orientation under the chitin chains driving. The design concept achieves multiple noncovalent assembly crosslinks (chitin–chitin, chitin–TA, and chitin–TA–2D) and biomimetic anisotropic nanofibrous morphology, leading to the superior mechanical performance. The anisotropic chitin–TA/brushite hydrogel effectively accelerates bone regeneration by promoting cell osteogenic differentiation and directional migration, showing potential in tissue engineering. It is anticipated that the noncovalent mediated assembly concept could be used to fabricate other polymer based composite anisotropic hydrogels for diverse applications. Abstract : A tannic acid noncovalent mediated assembly strategy is developed to simultaneously improve the chitin chain mobility and enhance the interfacial interaction for achieving strong anisotropic chitin/2D materials hydrogels via mechanical deformation. The anisotropic chitin–tannic acid/brushite hydrogel effectively accelerates bone repair by promoting the cells, osteogenic differentiation and directional migration, showing potential in tissue engineering.